The Production, Comprehension and Processing of Welsh Grammatical Gender in Welsh-English Adult Bilinguals - TESNI GALVIN (2024)
Grammatical gender in Welsh is a persistent area of difficulty in child bilingual acquisition, yet it is well-established in adult control data (Binks & Thomas, 2019; Sharp, 2012). Typically, gender has been investigated through its use in combination with the mutation system. This thesis extends these findings to the use of gender in Welsh-English bilingual adults and establishes whether gender is as robust when in conjunction with mutations or independent of mutations. The first experiment explored the comprehension and production of gender in 40 Welsh adult bilinguals and considered language dominance and Welsh linguistic proficiency. The results from a comprehension task showed fairly accurate use of gender in comprehension, with similar performance when gender is independent of mutations and in conjunction with mutations. The results from a production task revealed that the bilinguals have a good productive command of gender when it is marked via numerals. There is also evidence to suggest stronger performance for the production of nouns in numeral-noun contexts, when gender is not involved with mutations, than when gender is in conjunction with mutations. Welsh linguistic proficiency predicted better performance in both comprehension and production tasks, while language dominance did not. The follow-up experiment investigated the processing of gender in 21/40 Welsh bilinguals and considered cognitive and environmental individual differences. The results showed evidence of sensitivity to determiner-noun gender agreement errors when gender was encoded through mutations via the determiner ‘y’, but not when gender was in conjunction with mutations nor independent of mutations. There was no evidence to suggest that any of the individual difference variables predicted increased sensitivity to gender agreement errors in Welsh, despite some variables predicting overall faster reading times in the bilinguals. These findings demonstrate that Welsh adult bilinguals from a more diverse population than those tested previously made use of gender in comprehension and production, and processed gender agreement errors during real time.